A damage mechanical model applied to analysis of mechanical properties of jointed rock masses. (February 2019) - Yang, Wendong; Zhang, Qianbing; Ranjith, P.G.; Yu, Rangang; Luo, Guangyu; Huang, Chenchen; Wang, Gang
Highlights: The state of joints distributed in rock masses can be represented by the damage tensor. The new constitutive model was applied in FLAC 3D . This damage model can be used to simulate the non-linear response of the rock masses. Abstract: The mechanical properties of jointed rock masses significantly affect the long-term behaviour and safety of engineering projects. In this paper, a damage mechanical theory is adopted to deal with some sets of joints distributed in rock masses. Based on the geometrical distribution of joints, a damage model which considers the influence of normal vector and area density of joints is used to describe the discontinuities. This damage model is programmed in finite difference software FLAC 3D, and an example of jointed rock masses is used to verify the validity of the model, which shows that this model can well reflect the influence of joint angle and joint density. Finally, we use this model to predict the displacements and damage zones in the rock masses surrounding an underground cavern. The simulation results show a good agreement with field measurements.